2014
DOI: 10.1039/c4tc00343h
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the surface wettability of the polymer dielectric for improved resolution of inkjet-printed electrodes and patterned channel regions in low-voltage solution-processed organic thin film transistors

Abstract: A facile method for realizing both inkjet printed electrodes with improved resolution and patterned semiconductor islands was developed to fabricate all solution processed low-voltage organic thin film transistors (OTFTs). By reducing the surface wettability of the polymer gate dielectric layer through coating of a self-assembled monolayer (SAM), fine and narrow inkjet printed source/drain electrodes (a line width of about 35 mm) and short channels (about 15 mm) were formed with very good yield and uniformity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…Functionalized pentacene with side chains was therefore synthesized to achieve face-to-face molecular stacking [88], [175]. By using TIPS-pentacene blended with PS, Guo et al demonstrated low-voltage organic TFTs with reduced trap density [176]- [178]. These functionalization methods were also applicable to other organic semiconductors, such as BTBT [179], DNTT [180], and dithieno [2,3- [181].…”
Section: ) Reduced Trap Densitymentioning
confidence: 99%
“…Functionalized pentacene with side chains was therefore synthesized to achieve face-to-face molecular stacking [88], [175]. By using TIPS-pentacene blended with PS, Guo et al demonstrated low-voltage organic TFTs with reduced trap density [176]- [178]. These functionalization methods were also applicable to other organic semiconductors, such as BTBT [179], DNTT [180], and dithieno [2,3- [181].…”
Section: ) Reduced Trap Densitymentioning
confidence: 99%
“…Then the contact angle turns to be the only alternatively optimized parameter, which is relevant to surface energy of the substrate and also the material ink. An effective method to modulate the surface wettability of the PVA would be using a fluoroalkyl silanes-trichloro(1H,1H,2H,2H-perfluorooctyl)silane (FOTS) self-assembled monolayers (SAMs) [64]. It can be seen that the PVA surface became much less wettable after FOTS modification with the measured water contact angle increasing from 54° to 118° and ink contact angle from 15° to 52°, respectively, as shown in Figure 4(a).…”
Section: Inkjet-printed Fine Silver Electrodes For Otftsmentioning
confidence: 99%
“…For that purpose, patterning of the channel layer is necessary to eliminate parasitic leakage and reduce crosstalk among neighboring devices. Various patterning techniques have been developed including dry-etching with photoresist mask [6], inkjet printing [7], laser patterning [8] and self-organization [9]. Considering the achievable feature resolution and process accuracy, dry-etching with photolithographic patterned photoresist mask is still a preferred Manuscript choice, which also benefits from the well-established manufacturing facilities in the industry [10].…”
Section: Introductionmentioning
confidence: 99%